AI & I : An intellectual history of artificial intelligence - Charniak, Eugene (Cambridge, Massachusetts: London, England: The Mitt Press, 2024)
"An intellectual history of the first 50 years of AI written by a major figure who has been involved since AI's inception"
Keywords: Artificial Intelligence. -- History